2005
DOI: 10.1080/10920277.2005.10596182
|View full text |Cite
|
Sign up to set email alerts
|

A Model for Coronary Heart Disease and Stroke with Applications to Critical Illness Insurance Underwriting I: The Model

Abstract: In Part I we constructed a model for the development of coronary heart disease (CHD) or stroke that either incorporates, or includes pathways through, the major risk factors of interest when underwriting for critical illness (CI) insurance. In Part II we extend this model to include other critical illnesses, for example, cancers and kidney failure, and describe some applications of the model. In particular, we discuss CI premium ratings for applicants with combinations of some or all of high body mass index, s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 24 publications
1
9
0
Order By: Relevance
“…Law, Wald & Rudnicka (2003) state that: "... cohort studies showed no association between serum cholesterol concentrations and stroke.'' This is consistent with the findings of Macdonald et al (2003), based on data from the Framingham Heart Study. However, Law, Wald & Rudnicka (2003) also report what they refer to as a 'paradox', in that earlier studies "... showed that statins reduced the incidence of stroke by about 30%.''…”
Section: Drug Treatments For Cardiovascular Diseasesupporting
confidence: 92%
“…Law, Wald & Rudnicka (2003) state that: "... cohort studies showed no association between serum cholesterol concentrations and stroke.'' This is consistent with the findings of Macdonald et al (2003), based on data from the Framingham Heart Study. However, Law, Wald & Rudnicka (2003) also report what they refer to as a 'paradox', in that earlier studies "... showed that statins reduced the incidence of stroke by about 30%.''…”
Section: Drug Treatments For Cardiovascular Diseasesupporting
confidence: 92%
“…To date, no gene or set of genes has been shown to cause illnesses such as heart disease and diabetes, and the pathways to those diseases are complicated. However, there is evidence that common chronic diseases tend to aggregate within a family (Macdonald, Waters, & Wekwete, 2005), suggesting that certain conditions tend to “run” within families. The economic model suggests that one's genetic endowment is part of one's available resources.…”
mentioning
confidence: 99%
“…Macdonald et al (2005a;2005b) modelled CHD using three risk factors assumed to be static (sex, smoking status and body mass index) and three assumed to be dynamic (i.e. Macdonald et al (2005a;2005b) modelled CHD using three risk factors assumed to be static (sex, smoking status and body mass index) and three assumed to be dynamic (i.e.…”
Section: Multifactorial Disordersmentioning
confidence: 99%